Human Norovirus prevalence in Africa: a review of studies from 1990 to 2013. Issue 1 (9th November 2015) - Kabue, Jean Pierre; Meader, Emma; Hunter, Paul R.; Potgieter, Natasha
Abstract: Objectives: To assess the contribution of Human Norovirus to diarrhoeal diseases in Africa. Methods: We conducted a systematic review of the PubMed and EMBASE databases for published articles of Human Norovirus in Africa between 1990 and 2013. Data were extracted from selected studies and analysed. Results: A total of 208 eligible studies were identified, of which 55 (from 19 countries) met the inclusion criteria. Many cases were of sporadic gastroenteritis (70.9%) in children (82%), 65.4% of which were seen in an outpatient setting. Over half (59.4%) of the affected children were under 5 years of age. The pooled prevalence rate of Human NoV was 11% (95% CI 8–14%), and the meta‐analysis indicated significant heterogeneity between the studies. However, the conditional negative binomial regression could not clearly find the factors affecting the Human NoV prevalence rates reported. A close relationship was found between Human Norovirus strains from environmental and clinical samples. Conclusion: Unreported sporadic gastroenteritis cases of Human Norovirus are common in Africa. Most are community‐associated infections. Possible environmental transmission routes have been documented. Combined environmental and clinical studies are required for targeted actions to control transmission of Human Norovirus in Africa. Systematic surveillance of Human Norovirus is needed to measure the burden of Norovirus‐induced gastroenteritis in Africa and support any requirements for vaccine development.